A flame retardant and fire resistant silicone rubber material and preparation method thereof

By using composite flame retardant fillers and silane coupling agents in high-temperature vulcanized silicone rubber, combined with parallel plate capacitor technology, the problem of poor flame retardant performance in the existing technology is solved, and low-cost and efficient flame retardant and fire-resistant safety is achieved Performance and flexibility meet the requirements of green and environmentally friendly production.

CN118271850BActive Publication Date: 2024-12-13DONGGUAN TAIYA ELECTRONICS TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410243976.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-04
Publication Date
2024-12-13
Estimated Expiration
2044-03-04

AI Technical Summary

Technical Problem

The flame retardant performance of existing high-temperature vulcanized silicone rubber is poor, and high added amounts of flame retardant fillers are required to reach the UL94-V0 level, resulting in a decrease in overall quality, reduced flexibility, low production efficiency and increased equipment consumption, which cannot meet the green and environmentally friendly production. Require.

Method used

Using silicone rubber material with relatively low flame retardant filler addition, the composite flame retardant filler such as carbon-grafted ultrafine molybdenum disulfide, hexagonal boron nitride nanosheets, combined with silane coupling agent and platinum catalyst. Silicone rubber material with good flame retardant and fire safety performance and excellent flexibility performance was prepared, and carbon was grafted through the traction surface of parallel plate capacitors to improve flame retardant performance.

Benefits of technology

With a lower amount of flame retardant filler addition, silicone rubber materials achieve good flame retardant and fire safety performance and flexibility, while reducing production costs, meeting the concept of green and environmentally friendly production, simplifying the preparation process and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004725285520000151
    Figure BDA0004725285520000151
  • Figure BDA0004725285520000161
    Figure BDA0004725285520000161
Patent Text Reader

Abstract

The present application relates to the technical field of flat vulcanized silicone rubber materials, in particular to a flame retardant and fire-resistant silicone rubber material and a preparation method thereof. A flame retardant and fire-resistant silicone rubber material is prepared from the following raw materials in percentage by mass: 1‑5% hydrogenated silicone oil, 4‑6% vinyl silicone oil, 2‑4% hydroxy silicone oil, 18‑22% compounded flame retardant filler, 8‑12% carbon black, 0.5‑1.0% silane coupling agent, 0.1‑0.2% release agent, 0.1‑0.3% platinum catalyst, 0.1‑0.2% inhibitor, and the remainder is raw rubber. The silicone rubber material prepared in the present application has good flame retardancy and fire resistance at a relatively low amount of flame retardant filler added, while reducing the overall production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of flat vulcanized silicone rubber materials, and in particular to a flame retardant and fire-resistant silicone rubber material and a preparation method thereof. Background Art

[0002] High temperature vulcanized silicone rubber has good high temperature resistance, low temperature resistance, weather resistance, electrical properties, physical mechanical strength, oil resistance, chemical corrosion resistance, physiological inertness and other advantages, and is widely used in automobile manufacturing, aviation, biomedicine, electronic appliances and other fields. The preparation method of high temperature vulcanized silicone rubber is as follows: a certain ratio of raw rubber (such as methyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, etc.), reinforcing filler (such as white carbon black, carbon black, silicon powder, etc.), vulcanizing agent (sulfur,) and other additives are mixed evenly in a kneading machine, and then placed at high temperature (110-170℃) for vulcanization molding to obtain an elastomer-high temperature vulcanized silicone rubber.

[0003] However, the flame retardant properties of current high temperature vulcanized silicone rubber are relatively poor, and its limiting oxygen index is less than 25%, which limits its application in places with flame retardant requirements. In order to improve the flame retardant properties of high temperature vulcanized silicone rubber, it is usually necessary to add at least 30-40wt% of flame retardant filler to make the flame retardant properties of the prepared high temperature vulcanized silicone rubber reach UL94-V0 level.

[0004] Although high addition of flame retardant fillers can give it good flame retardant properties, it increases the overall quality of high temperature vulcanized silicone rubber and its flexibility also decreases to a certain extent. In addition, high addition of flame retardant fillers also increases the overall processing difficulty of high temperature vulcanized silicone rubber. It takes a longer time in the kneading machine to complete the uniform mixing of fillers and the vulcanization molding stage, which reduces the overall production efficiency and puts higher requirements on the kneading machine. Long mixing time leads to increased equipment wear of the kneading machine. The kneading machine screw requires greater torque force, which increases the output power of the kneading machine. The overall production energy consumption of high temperature vulcanized silicone rubber is also relatively high, which cannot meet the current green and environmentally friendly production concept.

[0005] In response to the flame retardant technical defects of the above-mentioned high-temperature vulcanized silicone rubber, the applicant provides a flame retardant and fire-resistant silicone rubber material and a preparation method thereof, which can ensure that the prepared silicone rubber material has good flame retardant and fire safety performance at a relatively low flame retardant filler addition amount, while reducing the overall production cost and meeting the current green and environmentally friendly production concept. Summary of the invention

[0006] In order to solve the above technical problems, the present application provides a flame retardant and fire resistant silicone rubber material and a preparation method thereof.

[0007] The flame retardant and fire resistant silicone rubber material provided in the present application is realized by the following technical scheme:

[0008] A flame retardant and fire-resistant silicone rubber material is prepared from the following raw materials in percentage by mass: 1-5% hydrogenated silicone oil, 4-6% vinyl silicone oil, 2-4% hydroxy silicone oil, 18-22% compound flame retardant filler, 8-12% carbon black, 0.5-1.0% silane coupling agent, 0.1-0.2% release agent, 0.1-0.3% platinum catalyst, 0.1-0.2% inhibitor, and the balance is raw rubber; the raw rubber is at least one of methyl silicone rubber, methyl vinyl silicone rubber, and methyl phenyl vinyl silicone rubber; the silane coupling agent is at least one of methacryloyloxysilane and vinyl silane; the release agent is at least one of zinc stearate, calcium stearate, and barium stearate. at least one of; the inhibitor is at least one of 3-methyl-1-butyne-3-ol, 3-methyl-1-pentyne-3-ol, 3,5-dimethyl-1-hexyne-3-ol, and 1-ethynyl-1-cyclohexanol; the composite flame retardant filler is composed of at least one of ultrafine molybdenum disulfide with surface grafted carbon, hexagonal boron nitride nanosheets with ultrafine aluminum nitride powder, ultrafine spherical alumina powder, ultrafine silicon nitride powder, nitrogen-phosphorus flame retardant FR-103, nano-calcium carbonate, ultrafine zinc borate, ultrafine antimony trioxide, ultrafine aluminum hydroxide, ultrafine magnesium hydroxide, nano-zinc oxide, ultrafine zinc stannate, ultrafine zirconium oxide, hollow glass microspheres, melamine cyanurate, ultrafine graphite powder, and toluene diphenyl phosphate.

[0009] The silicone rubber material prepared in the present application still has good flame retardant and fire safety performance and relatively excellent flexibility at a relatively low flame retardant filler addition amount, while reducing the overall production cost and meeting the current green and environmentally friendly production concept.

[0010] Furthermore, it is prepared from the following raw materials in percentage by mass: 3-4% hydrogenated silicone oil, 5-6% vinyl silicone oil, 2-3% hydroxy silicone oil, 20% compound flame retardant filler, 10% carbon black, 0.6-0.8% silane coupling agent, 0.2% mold release agent, 0.2-0.3% platinum catalyst, 0.1-0.2% inhibitor, and the remainder is raw rubber; the raw rubber is composed of methyl vinyl silicone rubber and methyl phenyl vinyl silicone rubber in a mass ratio of (7-8):(2-3); the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; the mold release agent is zinc stearate; and the inhibitor is 3,5-dimethyl-1-hexyn-3-ol.

[0011] Furthermore, the composite flame retardant filler is made of the following raw materials in percentage by mass: 15-25% of ultrafine molybdenum disulfide with carbon grafted on the surface, 10-20% of hexagonal boron nitride nanosheets, 10-30% of ultrafine spherical alumina powder, 1-5% of ultrafine silicon nitride powder, 5-10% of nano calcium carbonate, 5-10% of nitrogen-phosphorus flame retardant FR-103, 5-10% of ultrafine aluminum hydroxide, 5-10% of ultrafine magnesium hydroxide, 0.5-3% of nano zinc oxide, and the remainder is hollow glass microspheres; the carbon in the ultrafine molybdenum disulfide with carbon grafted on the surface is graphene and / or carbon nanotubes.

[0012] Furthermore, the composite flame retardant filler is made of the following raw materials in percentage by mass: 20-25% of ultrafine molybdenum disulfide with surface grafted carbon, 15-20% of hexagonal boron nitride nanosheets, 15-20% of ultrafine spherical alumina powder, 2-4% of ultrafine silicon nitride powder, 6-8% of nano calcium carbonate, 6-8% of nitrogen-phosphorus flame retardant FR-103, 6-8% of ultrafine aluminum hydroxide, 6-8% of ultrafine magnesium hydroxide, 0.8-1.5% of nano zinc oxide, and the remainder is hollow glass microspheres.

[0013] Furthermore, the composite flame retardant filler is made of the following raw materials in percentage by mass: 24% ultrafine molybdenum disulfide with surface grafted carbon, 16% hexagonal boron nitride nanosheets, 18% ultrafine spherical alumina powder, 3% ultrafine silicon nitride powder, 8% nano calcium carbonate, 6% nitrogen-phosphorus flame retardant FR-103, 6% ultrafine aluminum hydroxide, 6% ultrafine magnesium hydroxide, 1% nano zinc oxide, and 12% hollow glass microspheres.

[0014] By adopting the above technical solution, the overall comprehensive performance can be guaranteed while reducing the production cost.

[0015] Furthermore, the preparation method of the ultrafine molybdenum disulfide with carbon grafted on the surface is as follows: carbon and polyvinyl pyrrolidone are added to the prepared Ag(2E4MI)2Ac complex solution and mixed evenly, wherein the carbon is graphene and / or carbon nanotubes; the mass ratio of the carbon to the polyvinyl pyrrolidone is 1:(1.0-1.2), the mass ratio of the carbon to the Ag(2E4MI)2Ac complex solution is 1:(400-500), and the content of the Ag(2E4MI)2Ac complex in the Ag(2E4MI)2Ac complex solution is 1:(400-500). The amount is 0.5-2wt%, and then ultrafine molybdenum disulfide is added after ultrasonic dispersion for 4-6h and mixed evenly, the mass ratio of the ultrafine molybdenum disulfide to the carbon is (19-99):1, and ultrasonic dispersion is continued for 1-4h to obtain a dispersion liquid, and the obtained dispersion liquid is subjected to reduced pressure distillation to remove the organic solvent to obtain a solid, and the obtained solid is placed at 200-220°C for sintering treatment for 200-400min, and the sintered solid is placed in a planetary ball mill for planetary ball milling to obtain ultrafine molybdenum disulfide with surface grafted carbon having an average particle size D50 controlled at 50-500nm.

[0016] Furthermore, the carbon element is compounded from graphene and multi-walled carbon nanotubes; the mass ratio of the graphene to the multi-walled carbon nanotubes is 1:(3-4).

[0017] By adopting the above technical solution, the flame retardant and fireproof properties of the prepared silicone rubber material can be guaranteed.

[0018] Furthermore, the viscosity of the hydrogen-containing silicone oil is 20-160 mPa·s, and the hydrogen content is 0.028-0.12 wt%; the viscosity of the vinyl silicone oil is 50-2000 mPa·s, and the vinyl content is 0.08-0.80 MMOL / G; the viscosity of the hydroxy silicone oil is 20-70 cst, and the hydroxyl content is 1.25-10%; the viscosity-average molecular weight of the methyl vinyl silicone rubber is 400,000-950,000, and the vinyl content is 0.07-0.7%; the viscosity-average molecular weight of the methyl phenyl vinyl silicone rubber is 400,000-800,000, the phenyl content is 2.5-20%, and the vinyl content is 0.15-0.5%.

[0019] The present application provides a method for preparing a flame retardant and fire resistant silicone rubber material, which is achieved by the following scheme:

[0020] A method for preparing a flame retardant and fire resistant silicone rubber material comprises the following steps:

[0021] Step 1, placing accurately measured composite flame retardant filler and silane coupling agent in a kneader and pre-kneading for 15-30 minutes to obtain a composite flame retardant filler with surface modified by silane coupling agent;

[0022] Step 2: Heat-treat the accurately measured composite flame-retardant filler modified with a surface silane coupling agent, carbon black and raw rubber in a kneader at 180-200° C. for 150-180 min, mix them evenly, and cool them to room temperature for later use;

[0023] Step three, the rubber material in step two is mixed evenly with accurately measured release agent, platinum catalyst, inhibitor, hydrogen-containing silicone oil, vinyl silicone oil and hydroxy silicone oil on a planetary mixer to obtain a mixed rubber, and the obtained mixed rubber is transferred to a flat plate vulcanizer for flat plate compression vulcanization at 120-160°C to obtain a finished flame retardant and fire-resistant silicone rubber material.

[0024] The preparation method provided in this application is relatively simple, has low difficulty in implementation, and is easy to implement for industrial production.

[0025] Furthermore, after the mixed rubber obtained in step 3 is transferred to the flat plate vulcanizer, a parallel plate capacitor is set on the flat plate vulcanizer so that the mixed rubber is located between the two plates of the parallel plate capacitor, and the electric field direction of the parallel plate capacitor is perpendicular to the horizontal direction of the vulcanization plate of the flat plate vulcanizer, and the field strength E of the parallel plate capacitor is 2.0*10 3 -5.0*10 4 Newton / Coulomb, during the flat plate vulcanization process, the positive and negative poles of the power supply connected to the two plates in the parallel plate capacitor are cyclically exchanged every 400-600 seconds, and the duration is 90-120 minutes.

[0026] By adopting the above technical scheme, the ultrafine molybdenum disulfide with surface grafted carbon can be enriched on the upper and lower surfaces of the prepared silicone rubber material. When it is burned by external flames, a dense silicon dioxide protective layer can be formed on the surface, thereby improving the overall flame retardant and fire safety performance.

[0027] In summary, this application has the following advantages:

[0028] 1. The silicone rubber material prepared in this application still has good flame retardant and fire safety performance and relatively excellent flexibility at a relatively low flame retardant filler addition amount, while reducing the overall production cost and meeting the green and environmentally friendly production and manufacturing concept.

[0029] 2. The preparation method provided in this application is relatively simple, has low difficulty in implementation, and is easy to implement for industrial production. DETAILED DESCRIPTION

[0030] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with the examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve.

[0031] Example

[0032] A flame retardant and fire-resistant silicone rubber material is prepared from the following raw materials in percentage by mass: 1-5% of hydrogenated silicone oil, 4-6% of vinyl silicone oil, 2-4% of hydroxy silicone oil, 18-22% of compound flame retardant filler, 8-12% of carbon black, 0.5-1.0% of silane coupling agent, 0.1-0.2% of release agent, 0.1-0.3% of platinum catalyst, 0.1-0.2% of inhibitor, and the balance is raw rubber.

[0033] Furthermore, the flame retardant and fire-resistant silicone rubber material is prepared from the following raw materials in percentage by mass: 3-4% hydrogenated silicone oil, 5-6% vinyl silicone oil, 2-3% hydroxy silicone oil, 20% compound flame retardant filler, 10% carbon black, 0.6-0.8% silane coupling agent, 0.2% release agent, 0.2-0.3% platinum catalyst, 0.1-0.2% inhibitor, and the remainder is raw rubber.

[0034] The raw rubber is at least one of methyl silicone rubber, methyl vinyl silicone rubber and methyl phenyl vinyl silicone rubber.

[0035] Furthermore, the raw rubber is composed of methyl vinyl silicone rubber and methyl phenyl vinyl silicone rubber in a mass ratio of (7-8):(2-3).

[0036] The viscosity of hydrogen-containing silicone oil is 20-160 mPa·s, and the hydrogen content is 0.028-0.12 wt%.

[0037] The viscosity of vinyl silicone oil is 50-2000mPa·s, and the vinyl content is 0.08-0.80MMOL / G.

[0038] The viscosity of hydroxy silicone oil is 20-70cst, and the hydroxyl content is 1.25-10%.

[0039] The viscosity average molecular weight of methyl vinyl silicone rubber is 400,000-950,000, and the vinyl content is 0.07-0.7%. The viscosity average molecular weight of methyl phenyl vinyl silicone rubber is 400,000-800,000, and the phenyl content is 2.5-20%, and the vinyl content is 0.15-0.5%.

[0040] The silane coupling agent is at least one of methacryloxysilane and vinylsilane.

[0041] Furthermore, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane.

[0042] The release agent is at least one of zinc stearate, calcium stearate and barium stearate.

[0043] Furthermore, the release agent is zinc stearate.

[0044] The inhibitor is at least one of 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, and 1-ethynyl-1-cyclohexanol.

[0045] Furthermore, the inhibitor is 3,5-dimethyl-1-hexyn-3-ol.

[0046] The composite flame retardant filler is composed of at least one of ultrafine molybdenum disulfide with carbon grafted on the surface, hexagonal boron nitride nanosheets, ultrafine aluminum nitride powder, ultrafine spherical aluminum oxide powder, ultrafine silicon nitride powder, nitrogen-phosphorus flame retardant FR-103, nano calcium carbonate, ultrafine zinc borate, ultrafine antimony trioxide, ultrafine aluminum hydroxide, ultrafine magnesium hydroxide, nano zinc oxide, ultrafine zinc stannate, ultrafine zirconium oxide, hollow glass microspheres, melamine cyanurate, ultrafine graphite powder, and toluene diphenyl phosphate.

[0047] Furthermore, the composite flame retardant filler is made of the following raw materials in percentage by mass: 15-25% of ultrafine molybdenum disulfide with surface grafted carbon, 10-20% of hexagonal boron nitride nanosheets, 10-30% of ultrafine spherical alumina powder, 1-5% of ultrafine silicon nitride powder, 5-10% of nano calcium carbonate, 5-10% of nitrogen-phosphorus flame retardant FR-103, 5-10% of ultrafine aluminum hydroxide, 5-10% of ultrafine magnesium hydroxide, 0.5-3% of nano zinc oxide, and the remainder is hollow glass microspheres.

[0048] Furthermore, the composite flame retardant filler is made of the following raw materials in percentage by mass: 20-25% of ultrafine molybdenum disulfide with surface grafted carbon, 15-20% of hexagonal boron nitride nanosheets, 15-20% of ultrafine spherical alumina powder, 2-4% of ultrafine silicon nitride powder, 6-8% of nano calcium carbonate, 6-8% of nitrogen-phosphorus flame retardant FR-103, 6-8% of ultrafine aluminum hydroxide, 6-8% of ultrafine magnesium hydroxide, 0.8-1.5% of nano zinc oxide, and the remainder is hollow glass microspheres.

[0049] Preferred solution: The composite flame retardant filler is composed of 24% ultrafine molybdenum disulfide with carbon grafted on the surface, 16% hexagonal boron nitride nanosheets, 18% ultrafine spherical alumina powder, 3% ultrafine silicon nitride powder, 8% nano calcium carbonate, 6% nitrogen-phosphorus flame retardant FR-103, 6% ultrafine aluminum hydroxide, 6% ultrafine magnesium hydroxide, 1% nano zinc oxide, and 12% hollow glass microspheres.

[0050] The carbon in the ultrafine molybdenum disulfide with carbon grafted on the surface is graphene and / or carbon nanotube.

[0051] The preparation method of ultrafine molybdenum disulfide with carbon grafted on the surface is as follows: carbon and polyvinyl pyrrolidone are added to the prepared Ag(2E4MI)2Ac complex solution and mixed evenly, wherein the carbon is graphene and / or carbon nanotubes; further, the carbon is compounded by graphene and multi-walled carbon nanotubes; the mass ratio of graphene to multi-walled carbon nanotubes is 1:(3-4); the mass ratio of carbon to polyvinyl pyrrolidone is 1:(1.0-1.2), the mass ratio of carbon to Ag(2E4MI)2Ac complex solution is 1:(400-500), and the Ag(2E4MI)2Ac complex solution is 1:(400-500). The content of Ag(2E4MI)2Ac complex is 0.5-2wt%, and then ultrafine molybdenum disulfide is added after ultrasonic dispersion for 4-6h and mixed evenly, the mass ratio of ultrafine molybdenum disulfide to carbon is (19-99):1, and ultrasonic dispersion is continued for 1-4h to obtain a dispersion liquid, and the obtained dispersion liquid is subjected to reduced pressure distillation to remove the organic solvent to obtain a solid, and the obtained solid is placed at 200-220°C for sintering treatment for 200-400min, and the sintered solid is placed in a planetary ball mill for planetary ball milling to obtain ultrafine molybdenum disulfide with surface grafted carbon and an average particle size D50 controlled at 50-500nm.

[0052] A method for preparing a flame retardant and fire resistant silicone rubber material comprises the following steps:

[0053] Step 1, placing accurately measured composite flame retardant filler and silane coupling agent in a kneader and pre-kneading for 15-30 minutes to obtain a composite flame retardant filler with surface modified by silane coupling agent;

[0054] Step 2: Heat-treat the accurately measured composite flame-retardant filler modified with a surface silane coupling agent, carbon black and raw rubber in a kneader at 180-200° C. for 150-180 min, mix them evenly, and cool them to room temperature for later use;

[0055] Step three, the rubber material in step two is mixed evenly with accurately measured release agent, platinum catalyst, inhibitor, hydrogen-containing silicone oil, vinyl silicone oil and hydroxy silicone oil on a planetary mixer to obtain a mixed rubber, and the obtained mixed rubber is transferred to a flat plate vulcanizer for flat plate compression vulcanization at 120-160°C to obtain a finished flame retardant and fire-resistant silicone rubber material.

[0056] Furthermore, after the mixed rubber obtained in step 3 is transferred to the flat plate vulcanizer, a parallel plate capacitor is set on the flat plate vulcanizer so that the mixed rubber is located between the two plates of the parallel plate capacitor, and the electric field direction of the parallel plate capacitor is perpendicular to the horizontal direction of the vulcanization plate of the flat plate vulcanizer, and the field strength E of the parallel plate capacitor is 2.0*10 3 -5.0*10 4Newton / Coulomb, during the flat plate vulcanization process, the positive and negative poles of the power supply connected to the two plates in the parallel plate capacitor are cyclically exchanged every 400-600 seconds, and the duration is 90-120 minutes.

[0057] Example 1: A flame retardant and fire resistant silicone rubber material disclosed in the present application is made of the following raw materials in parts by weight:

[0058] 43.5 parts of methyl vinyl silicone rubber (methyl terminated rubber from Ningbo Daoruo Silicone Co., Ltd., model: DR-110-3, molecular weight 450,000-590,000, vinyl content 0.19-0.24wt%);

[0059] 14.5 parts of methylphenyl vinyl silicone rubber (methylphenyl vinyl silicone rubber IOTA 34 customized by Anhui IOTA Silicone Oil Co., Ltd., with a viscosity-average molecular weight of 600,000-650,000, a phenyl content of 8.5-9.0%, and a vinyl content of 0.3-0.35%);

[0060] 0.6 parts of γ-methacryloxypropyltrimethoxysilane KH570 (CAS: 2530-85-0);

[0061] 3.2 parts of hydrogen-containing silicone oil (terminated hydrogen-containing silicone oil D-30 from Keqi polymer materials, viscosity 35 mPa·s, hydrogen content 0.07 wt%);

[0062] 5.2 parts of vinyl silicone oil (Keqi polymer material V500, viscosity 500mPa·s, vinyl content 0.15MMOL / G);

[0063] 2.4 parts of hydroxy silicone oil (Keqi polymer material OH-007, viscosity 70cat, hydroxyl content 1.25wt%);

[0064] 10 parts of carbon black (Carbon Black 550, Hejian Jialong Rubber Products Co., Ltd.);

[0065] 0.2 parts of zinc stearate (CAS: 557-05-1);

[0066] 0.25 parts of platinum catalyst (platinum catalyst model SK-P050, brand Shenzhen Tianqi);

[0067] 0.15 parts of inhibitor-3,5-dimethyl-1-hexyn-3-ol (CAS: 107-54-0);

[0068] 20 parts of compound flame retardant filler.

[0069] The compound flame retardant filler contains 4.8 parts of ultrafine molybdenum disulfide with surface grafted carbon (self-made), 3.2 parts of hexagonal boron nitride nanosheets (average particle size 600nm, model CW-BN-002, Shanghai Chaowei Nano), 3.6 parts of ultrafine spherical alumina powder (DCA-01S, 12500 mesh / 1 micron, Dongguan Dongchao New Material Technology), 0.6 parts of ultrafine silicon nitride powder (α-phase silicon nitride powder, model NN-004-3, average particle size 1 micron, CAS: 1300-2-4, Qinghe County Chaotai Metal Materials), 1.6 parts of nano calcium carbonate (CAS: 14098-3-2, average particle size 200nm, Qinghe County Chaotai Metal Materials), 1.2 parts of nitrogen-phosphorus flame retardant FR-103 (purchased from Qingdao Xuting Chemical Co., Ltd.), 1.2 parts of ultrafine aluminum hydroxide (Jinan Yongchen Chemical, CAS: 21645-51-2, model ATH-1B, D50 = 1.61 microns), 1.2 parts of ultrafine magnesium hydroxide (particle size D50 <5um, model Q-KB-5, Weifang Lihe Powder Technology), 0.2 parts of nano zinc oxide (CAS: 1314-13-2, model HN-J50W, particle size 30nm, Hangzhou Hengna New Materials), 2.4 parts of hollow glass microspheres (US 3M hollow glass microspheres S15).

[0070] A method for preparing a flame retardant and fire resistant silicone rubber material comprises the following steps:

[0071] Step 1, the preparation method of ultrafine molybdenum disulfide with surface grafted carbon is as follows: first prepare Ag(2E4MI)2Ac complex solution: add 0.02 mol of 2-ethyl-4-methylimidazole 2E4MI (CAS: 931-36-2) and 0.01 mol of silver acetate AgAc (CAS: 563-63-3) into 400 mL of dichloromethane (CAS: 75-09-2), and stir magnetically at a speed of 240 r / min until the AgAc particles completely disappear to obtain a clear and transparent Ag(2E4MI)2Ac complex solution; add 0.8 g of multi-walled carbon nanotubes (Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, short high-purity multi-walled carbon nanotubes short MWCNTs, outer diameter 4-8nm, length 0.5-2um, model TNSMH0), 0.8g polyvinyl pyrrolidone were mixed evenly, ultrasonic power 1200W ultrasonic frequency 44kHz ultrasonic dispersion for 4h, 50g ultrafine molybdenum disulfide (model CW-MoS2-002, average particle size 50nm, near spherical crystal, Shanghai Chaowei Nano) was added and mixed evenly, mechanically stirred at a speed of 400r / min for 15min, and then ultrasonic dispersion was continued for 2h to obtain a dispersion liquid, the obtained dispersion liquid was subjected to reduced pressure distillation to remove the organic solvent to obtain a solid, the obtained solid was placed at 220°C for sintering treatment for 400min, and the sintered solid was placed in a planetary ball mill to obtain a solid with an average particle size of D 50 =200nm ultrafine molybdenum disulfide with multi-walled carbon nanotubes grafted on the surface;

[0072] It should be noted that: the selection of near-spherulite ultrafine molybdenum disulfide is better than the lamellar ultrafine molybdenum disulfide in improving the flame retardant and fire safety performance of the overall silicone rubber material. In the subsequent preparation process step five, a parallel plate capacitor will be used to pull the surface-grafted carbon ultrafine molybdenum disulfide. Under the action of the electric field, the surface-grafted carbon ultrafine molybdenum disulfide in the silicone rubber resin will be enriched on the surface. When the prepared silicone rubber material is ablated by external flames, the surface-enriched surface-grafted multi-walled carbon nanotubes ultrafine molybdenum disulfide decomposes to form a dense silicon dioxide protective layer, thereby improving the overall flame retardant and fire safety performance.

[0073] Step 2, placing 4.8 parts of ultrafine molybdenum disulfide with surface grafted carbon, 3.2 parts of hexagonal boron nitride nanosheets, 3.6 parts of ultrafine spherical aluminum oxide powder, 0.6 parts of ultrafine silicon nitride powder, 1.6 parts of nano calcium carbonate, 1.2 parts of nitrogen phosphorus flame retardant FR-103, 1.2 parts of ultrafine aluminum hydroxide, 1.2 parts of ultrafine magnesium hydroxide, 0.2 parts of nano zinc oxide, 2.4 parts of hollow glass microsphere silicon and 0.6 parts of γ-methacryloxypropyltrimethoxysilane KH570 in a kneader and pre-kneading for 20 minutes to obtain a composite flame retardant filler modified with a surface silane coupling agent;

[0074] Step three, heat-treat the accurately measured composite flame retardant filler modified with surface silane coupling agent in step two, 10 parts of carbon black, 43.5 parts of methyl vinyl silicone rubber, and 14.5 parts of methyl phenyl vinyl silicone rubber in a kneader at 180° C. for 180 min, mix them evenly, and cool them to room temperature for use.

[0075] Step 4: Mix the rubber material in step 3 with accurately measured 0.2 parts of zinc stearate, 0.25 parts of platinum catalyst, 0.15 parts of inhibitor 3,5-dimethyl-1-hexyn-3-ol, 3.2 parts of hydrogenated silicone oil, 5.2 parts of vinyl silicone oil, and 2.4 parts of hydroxy silicone oil on a planetary mixer to obtain a mixed rubber. The mixed rubber is transferred to a flat plate vulcanizer and vulcanized at 140°C. The specific operation method is as follows: After the mixed rubber is transferred to the flat plate vulcanizer, the flat plate vulcanizer is operated according to the parallel plate electric curing method. The container is made so that the mixed rubber on the flat plate of the flat plate vulcanizer is located between the two plates of the parallel plate capacitor, the distance between the two plates is 25 cm and the connection voltage is DC = 1000V, the electric field direction of the parallel plate capacitor is perpendicular to the horizontal direction of the vulcanization plate of the flat plate vulcanization, and during the flat plate vulcanization process, the positive and negative poles of the power supply connected to the two plates in the parallel plate capacitor are cyclically exchanged every 500s, the duration is 100min, and the total flat plate vulcanization time is 3.0h, and the finished flame retardant and fire-resistant silicone rubber material can be obtained.

[0076] The difference between Example 2 and Example 1 is that 14.5 parts of methylphenylvinyl silicone rubber in the flame retardant and fire resistant silicone rubber material formula are replaced by 14.5 parts of methyl silicone rubber.

[0077] The difference between Example 3 and Example 1 is that 0.6 parts of γ-methacryloxypropyltrimethoxysilane KH570 in the flame retardant and fire resistant silicone rubber material formula is replaced by 0.6 parts of vinyltriethoxysilane KH151.

[0078] The difference between Example 4 and Example 1 is that the flame retardant and fire-resistant silicone rubber material is made of the following raw materials in parts by mass: 45 parts of methyl vinyl silicone rubber; 15 parts of methylphenyl vinyl silicone rubber; 0.6 parts of γ-methacryloxypropyltrimethoxysilane KH570; 3.2 parts of hydrogenated silicone oil; 5.2 parts of vinyl silicone oil; 2.4 parts of hydroxy silicone oil; 10 parts of carbon black; 0.2 parts of zinc stearate; 0.25 parts of platinum catalyst, 0.15 parts of inhibitor-3,5-dimethyl-1-hexyn-3-ol; and 18 parts of compound flame retardant filler. Among them, 18 parts of compound flame retardant fillers contain 4.32 parts of ultrafine molybdenum disulfide with surface grafted carbon, 2.88 parts of hexagonal boron nitride nanosheets, 3.24 parts of ultrafine spherical alumina powder, 0.54 parts of ultrafine silicon nitride powder, 1.44 parts of nano calcium carbonate, 1.08 parts of nitrogen-phosphorus flame retardant FR-103, 1.08 parts of ultrafine aluminum hydroxide, 1.08 parts of ultrafine magnesium hydroxide, 0.18 parts of nano zinc oxide, and 2.16 parts of hollow glass microspheres.

[0079] The difference between Example 5 and Example 1 is that the flame retardant and fire-resistant silicone rubber material is made of the following raw materials in parts by mass: 42 parts of methyl vinyl silicone rubber; 14 parts of methylphenyl vinyl silicone rubber; 0.6 parts of γ-methacryloxypropyltrimethoxysilane KH570; 3.2 parts of hydrogenated silicone oil; 5.2 parts of vinyl silicone oil; 2.4 parts of hydroxy silicone oil; 10 parts of carbon black; 0.2 parts of zinc stearate; 0.25 parts of platinum catalyst, 0.15 parts of inhibitor-3,5-dimethyl-1-hexyn-3-ol; and 22 parts of compound flame retardant filler. Among them, 22 parts of compound flame retardant fillers contain 5.28 parts of ultrafine molybdenum disulfide with surface grafted carbon, 3.52 parts of hexagonal boron nitride nanosheets, 3.96 parts of ultrafine spherical alumina powder, 0.66 parts of ultrafine silicon nitride powder, 1.76 parts of nano calcium carbonate, 1.32 parts of nitrogen-phosphorus flame retardant FR-103, 1.32 parts of ultrafine aluminum hydroxide, 1.32 parts of ultrafine magnesium hydroxide, 0.22 parts of nano zinc oxide, and 2.64 parts of hollow glass microspheres.

[0080] The difference between Example 6 and Example 1 is that the preparation method of the ultrafine molybdenum disulfide with carbon grafted on the surface is as follows: first prepare the Ag(2E4MI)2Ac complex solution: add 0.02 mol of 2-ethyl-4-methylimidazole and 0.01 mol of silver acetate AgAc into 400 mL of dichloromethane, and stir magnetically at a speed of 240 r / min until the AgAc particles completely disappear to obtain a clear and transparent Ag(2E4MI)2Ac complex solution; add 0.8 g of graphene (Chinese Science) into the prepared Ag(2E4MI)2Ac complex solution. Chengdu Organic Chemistry Co., Ltd., three-dimensional graphene TN3DRGO), 0.8g polyvinyl pyrrolidone were mixed evenly, ultrasonic power 1200W ultrasonic frequency 44kHz ultrasonic dispersion for 5h, 50g ultrafine molybdenum disulfide was added and mixed evenly, mechanical stirring was carried out at a speed of 600r / min for 20min, and ultrasonic dispersion was continued for 3h to obtain a dispersion liquid, and the obtained dispersion liquid was subjected to reduced pressure distillation to remove the organic solvent to obtain a solid, and the obtained solid was placed at 210°C for sintering treatment for 400min, and the sintered solid was placed in a planetary ball mill to obtain a particle size of D 50 =200nm of ultrafine molybdenum disulfide with surface grafted graphene.

[0081] The difference between Example 7 and Example 1 is that the preparation method of the ultrafine molybdenum disulfide with surface grafted carbon is as follows: first prepare an Ag(2E4MI)2Ac complex solution: add 0.02 mol of 2-ethyl-4-methylimidazole and 0.01 mol of silver acetate AgAc to 400 mL of dichloromethane, and stir magnetically at a speed of 240 r / min until the AgAc particles completely disappear to obtain a clear and transparent Ag(2E4MI)2Ac complex solution; add 0.45 g of graphene (Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, three-dimensional graphene TN3DRGO), 0.45 g of multi-walled carbon nanotubes (Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, short high-purity multi-walled carbon nanotubes short MWCNTs, outer diameter 4-8nm, length 0.5-2um, model TNSMH0), 1.0g polyvinyl pyrrolidone were mixed evenly, ultrasonic power 1200W ultrasonic frequency 44kHz ultrasonic dispersion for 6h, 50g ultrafine molybdenum disulfide was added and mixed evenly, mechanical stirring was carried out at a speed of 600r / min for 30min, and ultrasonic dispersion was continued for 3h to obtain a dispersion liquid, the obtained dispersion liquid was subjected to reduced pressure distillation to remove the organic solvent to obtain a solid, the obtained solid was placed at 210°C for sintering treatment for 400min, and the sintered solid was placed in a planetary ball mill to obtain a particle size D 50 =200nm of ultrafine molybdenum disulfide with surface grafted graphene / multi-walled carbon nanotubes.

[0082] The difference between Example 8 and Example 1 is that 4.8 parts of the ultrafine molybdenum disulfide with surface grafted carbon in Example 1 in the composite flame retardant filler are replaced by 2.4 parts of the ultrafine molybdenum disulfide with surface grafted carbon in Example 1 and 2.4 parts of the ultrafine molybdenum disulfide with surface grafted carbon in Example 6.

[0083] The difference between Example 9 and Example 1 is that 20 parts of the composite flame retardant filler contain 2 parts of ultrafine molybdenum disulfide with surface grafted carbon, 2 parts of hexagonal boron nitride nanosheets, 2 parts of ultrafine spherical alumina powder, 2 parts of ultrafine silicon nitride powder, 2 parts of nano calcium carbonate, 2 parts of nitrogen-phosphorus flame retardant FR-103, 2 parts of ultrafine aluminum hydroxide, 2 parts of ultrafine magnesium hydroxide, 2 parts of nano zinc oxide, and 2 parts of hollow glass microspheres.

[0084] The difference between Example 10 and Example 1 is that 20 parts of the composite flame retardant filler contain 2.4 parts of ultrafine molybdenum disulfide with surface grafted carbon, 3.6 parts of hexagonal boron nitride nanosheets, 5 parts of ultrafine spherical alumina powder, 0.6 parts of ultrafine silicon nitride powder, 2 parts of nano calcium carbonate, 1.2 parts of nitrogen-phosphorus flame retardant FR-103, 1 part of ultrafine aluminum hydroxide, 1 part of ultrafine magnesium hydroxide, 0.2 parts of nano zinc oxide, and 3 parts of hollow glass microspheres.

[0085] The difference between Example 11 and Example 1 is that 20 parts of the composite flame retardant filler contain 3 parts of ultrafine molybdenum disulfide with surface grafted carbon, 4 parts of hexagonal boron nitride nanosheets, 4 parts of ultrafine spherical alumina powder, 0.6 parts of ultrafine silicon nitride powder, 2 parts of nano calcium carbonate, 1.2 parts of nitrogen-phosphorus flame retardant FR-103, 1 part of ultrafine aluminum hydroxide, 1 part of ultrafine magnesium hydroxide, 0.2 parts of nano zinc oxide, and 3 parts of hollow glass microspheres.

[0086] The difference between Example 12 and Example 1 is that 20 parts of the composite flame retardant filler contain 4 parts of ultrafine molybdenum disulfide with surface grafted carbon, 3.2 parts of hexagonal boron nitride nanosheets, 4 parts of ultrafine spherical alumina powder, 0.6 parts of ultrafine silicon nitride powder, 2 parts of nano calcium carbonate, 1.2 parts of nitrogen-phosphorus flame retardant FR-103, 1.6 parts of ultrafine aluminum hydroxide, 1.2 parts of ultrafine magnesium hydroxide, 0.2 parts of nano zinc oxide, and 2 parts of hollow glass microspheres.

[0087] The difference between Example 13 and Example 1 is that 20 parts of the composite flame retardant filler contain 5 parts of ultrafine molybdenum disulfide with surface grafted carbon, 3 parts of hexagonal boron nitride nanosheets, 3.6 parts of ultrafine spherical alumina powder, 0.6 parts of ultrafine silicon nitride powder, 1.6 parts of nano calcium carbonate, 1.2 parts of nitrogen-phosphorus flame retardant FR-103, 1.6 parts of ultrafine aluminum hydroxide, 1.2 parts of ultrafine magnesium hydroxide, 0.2 parts of nano zinc oxide, and 2 parts of hollow glass microspheres.

[0088] The difference between Example 14 and Example 1 is that 20 parts of the composite flame retardant filler contain 5.6 parts of ultrafine molybdenum disulfide with surface grafted carbon, 4.4 parts of hexagonal boron nitride nanosheets, 3.2 parts of ultrafine spherical alumina powder, 0.6 parts of ultrafine silicon nitride powder, 1 part of nano calcium carbonate, 1 part of nitrogen-phosphorus flame retardant FR-103, 1 part of ultrafine aluminum hydroxide, 1 part of ultrafine magnesium hydroxide, 0.2 parts of nano zinc oxide, and 2 parts of hollow glass microspheres.

[0089] The difference between Example 15 and Example 1 is: Step 4, the rubber material in Step 3 is evenly mixed with accurately measured 0.2 parts of zinc stearate, 0.25 parts of platinum catalyst, 0.15 parts of inhibitor 3,5-dimethyl-1-hexyn-3-ol, 3.2 parts of hydrogenated silicone oil, 5.2 parts of vinyl silicone oil, and 2.4 parts of hydroxyl silicone oil on a planetary mixer to obtain a mixed rubber, and the obtained mixed rubber is transferred to a flat plate vulcanizer and vulcanized at 140°C for 3.0 hours to obtain a finished flame retardant and fire-resistant silicone rubber material.

[0090] The difference between Comparative Example 1 and Example 1 is that the flame retardant and fire-resistant silicone rubber material is made of the following raw materials in parts by mass: 47.25 parts of methyl vinyl silicone rubber; 15.75 parts of methylphenyl vinyl silicone rubber; 0.6 parts of γ-methacryloxypropyltrimethoxysilane KH570; 3.2 parts of hydrogenated silicone oil; 5.2 parts of vinyl silicone oil; 2.4 parts of hydroxy silicone oil; 10 parts of carbon black; 0.2 parts of zinc stearate; 0.25 parts of platinum catalyst; 0.15 parts of inhibitor-3,5-dimethyl-1-hexyn-3-ol; and 15 parts of compound flame retardant filler. Among them, 15 parts of compound flame retardant fillers contain 3.6 parts of ultrafine molybdenum disulfide with surface grafted carbon, 2.4 parts of hexagonal boron nitride nanosheets, 2.7 parts of ultrafine spherical alumina powder, 0.45 parts of ultrafine silicon nitride powder, 1.2 parts of nano calcium carbonate, 0.9 parts of nitrogen-phosphorus flame retardant FR-103, 0.9 parts of ultrafine aluminum hydroxide, 0.9 parts of ultrafine magnesium hydroxide, 0.15 parts of nano zinc oxide, and 1.8 parts of hollow glass microspheres.

[0091] The difference between Comparative Example 2 and Example 1 is that the flame retardant and fire-resistant silicone rubber material is made of the following raw materials in parts by mass: 39.75 parts of methyl vinyl silicone rubber; 13.25 parts of methylphenyl vinyl silicone rubber; 0.6 parts of γ-methacryloxypropyltrimethoxysilane KH570; 3.2 parts of hydrogenated silicone oil; 5.2 parts of vinyl silicone oil; 2.4 parts of hydroxy silicone oil; 10 parts of carbon black; 0.2 parts of zinc stearate; 0.25 parts of platinum catalyst; 0.15 parts of inhibitor-3,5-dimethyl-1-hexyn-3-ol; and 25 parts of compound flame retardant filler. Among them, 25 parts of compound flame retardant fillers contain 6 parts of ultrafine molybdenum disulfide with surface grafted carbon, 4 parts of hexagonal boron nitride nanosheets, 4.5 parts of ultrafine spherical alumina powder, 0.75 parts of ultrafine silicon nitride powder, 2 parts of nano calcium carbonate, 1.5 parts of nitrogen-phosphorus flame retardant FR-103, 1.5 parts of ultrafine aluminum hydroxide, 1.5 parts of ultrafine magnesium hydroxide, 0.25 parts of nano zinc oxide, and 3 parts of hollow glass microspheres.

[0092] The difference between Comparative Example 3 and Example 1 is that 4.8 parts of ultrafine molybdenum disulfide with surface grafted carbon in the composite flame retardant filler is replaced by 4.8 parts of ultrafine molybdenum disulfide, that is, the ultrafine molybdenum disulfide is not subjected to surface grafted carbon modification treatment.

[0093] The difference between Comparative Example 4 and Example 1 is that 20 parts of the composite flame retardant filler contain 5 parts of melamine cyanurate, 5 parts of nitrogen-phosphorus flame retardant FR-103, 5 parts of ultrafine aluminum hydroxide, and 5 parts of ultrafine magnesium hydroxide.

[0094] The difference between Comparative Example 5 and Example 1 is that the silicone rubber material is made of the following raw materials in parts by mass: 30 parts of methyl vinyl silicone rubber; 10 parts of methyl phenyl vinyl silicone rubber; 0.6 parts of γ-methacryloxypropyl trimethoxysilane KH570; 3.2 parts of hydrogenated silicone oil; 5.2 parts of vinyl silicone oil; 2.4 parts of hydroxy silicone oil; 10 parts of carbon black; 0.2 parts of zinc stearate; 0.25 parts of platinum catalyst; 0.15 parts of inhibitor-3,5-dimethyl-1-hexyn-3-ol; 38 parts of flame retardant filler. Among them, 38 parts of flame retardant filler contains 8 parts of melamine cyanurate, 10 parts of nitrogen phosphorus flame retardant FR-103, 10 parts of ultrafine aluminum hydroxide, and 10 parts of ultrafine magnesium hydroxide.

[0095] The difference between Comparative Example 6 and Example 1 is that 20 parts of the composite flame retardant filler contain 4.8 parts of ultrafine molybdenum disulfide with surface grafted carbon, 5 parts of ultrafine spherical alumina powder, 0.6 parts of ultrafine silicon nitride powder, 1 part of nano calcium carbonate, 2 parts of nitrogen-phosphorus flame retardant FR-103, 2 parts of ultrafine aluminum hydroxide, 2 parts of ultrafine magnesium hydroxide, 0.2 parts of nano zinc oxide, and 2.4 parts of hollow glass microspheres.

[0096] The difference between Comparative Example 7 and Example 1 is that 20 parts of the composite flame retardant filler contain 6 parts of hexagonal boron nitride nanosheets, 4 parts of ultrafine spherical alumina powder, 0.6 parts of ultrafine silicon nitride powder, 0.8 parts of nano calcium carbonate, 2 parts of nitrogen-phosphorus flame retardant FR-103, 2 parts of ultrafine aluminum hydroxide, 2 parts of ultrafine magnesium hydroxide, 0.2 parts of nano zinc oxide, and 2.4 parts of hollow glass microspheres.

[0097] The difference between Comparative Example 8 and Example 1 is that 20 parts of the composite flame retardant filler contain 4 parts of melamine cyanurate, 4 parts of ultrafine molybdenum disulfide, 0.6 parts of ultrafine silicon nitride powder, 2 parts of nano calcium carbonate, 2 parts of nitrogen phosphorus flame retardant FR-103, 2 parts of ultrafine aluminum hydroxide, 2 parts of ultrafine magnesium hydroxide, 0.2 parts of nano zinc oxide, and 2.4 parts of hollow glass microspheres.

[0098] Performance testing: Tensile strength and elongation at break of silicone rubber materials: tested according to GB / T 528-2009. Limiting oxygen index of silicone rubber materials: tested according to GB / T 10707-2008. Flame retardant grade of silicone rubber materials: tested according to UL-94 standard.

[0099] Table 1 Flame retardant and fire safety test parameters of silicone rubber materials in Examples 1-15 and Comparative Examples 1-8

[0100]

[0101]

[0102] It can be seen from Example 1 and Example 15 and Table 1 that the preparation method of the present application uses a parallel electric field to pull the ultrafine molybdenum sulfide of the surface grafted carbon in the silicone rubber material to adjust the concentration of the ultrafine molybdenum sulfide of the surface grafted carbon in its surface appendages, which has a positive effect on the flame retardant and fire safety performance of the prepared silicone rubber material.

[0103] Combining Example 1 with Example 2 and Table 1, it can be seen that the silicone rubber material prepared by compounding methyl vinyl silicone rubber and methyl phenyl vinyl silicone rubber as raw rubber has relatively better flame retardant and fire safety performance, while the silicone rubber material prepared by compounding methyl silicone rubber and methyl vinyl silicone rubber as raw rubber only has certain advantages in flexibility.

[0104] In combination with Examples 1-15 and Comparative Examples 1-8 and Table 1, it can be seen that the addition amount of the compound flame retardant filler is controlled at 18-22wt% which is more appropriate; further, the addition amount of the compound flame retardant filler is 20wt% and the compound flame retardant filler is made of the following raw materials in percentage by mass: 24% ultrafine molybdenum sulfide with surface grafted carbon, 16% hexagonal boron nitride nanosheets, 18% ultrafine spherical alumina powder, 3% ultrafine silicon nitride powder, 8% nano calcium carbonate, 6% nitrogen phosphorus flame retardant FR-103, 6% ultrafine aluminum hydroxide, 6% ultrafine magnesium hydroxide, 1% nano zinc oxide, and 12% hollow glass microspheres.

[0105] It can be seen from Example 1 and Comparative Example 3 and Table 1 that the composite flame retardant filler formed by the composite of ultrafine molybdenum sulfide with surface grafted carbon has a positive effect on improving the flame retardant and fire safety performance and mechanical strength of the prepared silicone rubber material.

[0106] It can be seen from Examples 1-15 and Comparative Examples 4-5 and Table 1 that the silicone rubber material prepared when the addition amount of the composite flame retardant filler is 20wt% has relatively good flame retardant and fire safety performance. Compared with the silicone rubber material in Comparative Examples 4-5, the present application can ensure that the prepared silicone rubber material has good flame retardant and fire safety performance at a relatively low flame retardant filler addition amount, while reducing the overall production cost and meeting the current green and environmentally friendly production concept.

[0107] The thermal conductivity of the silicone rubber material in Example 1 was tested, and its thermal conductivity was 2.04 W / (m·K); the thermal conductivity of Example 5 was 2.12 W / (m·K); and the thermal conductivity of Comparative Example 4 was 0.27 W / (m·K), and the thermal conductivity of Comparative Example 5 was 0.28 W / (m·K). It can be seen from Examples 1-15 and Comparative Examples 1-8 and Table 1 that the silicone rubber material formula provided in the present application has a corresponding optimization of its preparation process, and the high thermal conductivity insulating particles in the composite flame retardant filler can optimize the overall thermal conductivity of the silicone rubber, which is convenient for rapid and uniform heat dissipation in the flat vulcanization section, and improves the efficiency of flat vulcanization molding.

[0108] In summary, the silicone rubber material prepared in the present application still has good flame retardant and fire safety performance and relatively excellent flexibility at a relatively low flame retardant filler addition amount, while reducing production costs and meeting the green and environmentally friendly production concept.

[0109] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A flame retardant and fire resistant silicone rubber material, characterized by: The invention is prepared from the following raw materials in the following mass percentages: 1-5% hydrogenated silicone oil, 4-6% vinyl silicone oil, 2-4% hydroxy silicone oil, 18-22% compound flame retardant filler, 8-12% carbon black, 0.5-1.0% silane coupling agent, 0.1-0.2% release agent, 0.1-0.3% platinum catalyst, 0.1-0.2% inhibitor, and the balance is raw rubber; the raw rubber is at least one of methyl silicone rubber, methyl vinyl silicone rubber, and methylphenyl vinyl silicone rubber; the silane coupling agent is at least one of methacryloxysilane and vinyl silane; the release agent is at least one of zinc stearate, calcium stearate, and barium stearate; and the inhibitor is at least one of 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, and 1-ethynyl-1-cyclohexanol; The composite flame retardant filler is made of the following raw materials in percentage by mass: 15-25% of ultrafine molybdenum disulfide with surface grafted carbon, 10-20% of hexagonal boron nitride nanosheets, 10-30% of ultrafine spherical alumina powder, 1-5% of ultrafine silicon nitride powder, 5-10% of nano calcium carbonate, 5-10% of nitrogen-phosphorus flame retardant FR-103, 5-10% of ultrafine aluminum hydroxide, 5-10% of ultrafine magnesium hydroxide, 0.5-3% of nano zinc oxide, and the balance is hollow glass microspheres; The preparation method of the surface-grafted carbon ultrafine molybdenum disulfide is as follows: carbon and polyvinyl pyrrolidone are added to the prepared Ag(2E4MI)2Ac complex solution and mixed evenly; the mass ratio of the carbon and polyvinyl pyrrolidone is 1:(1.0-1.2), the mass ratio of the carbon and the Ag(2E4MI)2Ac complex solution is 1:(400-500), and the content of the Ag(2E4MI)2Ac complex in the Ag(2E4MI)2Ac complex solution is 0.5-2wt%. Then, after ultrasonic dispersion for 4-6 hours, ultrafine molybdenum disulfide is added and mixed evenly, wherein the mass ratio of the ultrafine molybdenum disulfide to the carbon is (19-99):1, and ultrasonic dispersion is continued for 1-4 hours to obtain a dispersion liquid, and the obtained dispersion liquid is subjected to reduced pressure distillation to remove the organic solvent to obtain a solid, and the obtained solid is placed at 200-220° C. for 200-400 minutes. The sintered solid is placed in a planetary ball mill and planetary ball milled to obtain ultrafine molybdenum disulfide with surface grafted carbon having an average particle size D50 controlled at 50-500 nm; The carbon is compounded by graphene and multi-walled carbon nanotubes; the mass ratio of the graphene to the multi-walled carbon nanotubes is 1:(3-4).

2. The flame-retardant and fire-resistant silicone rubber material according to claim 1, characterized in that: The invention is prepared from the following raw materials in percentage by mass: 3-4% of hydrogenated silicone oil, 5-6% of vinyl silicone oil, 2-3% of hydroxy silicone oil, 20% of compound flame retardant filler, 10% of carbon black, 0.6-0.8% of silane coupling agent, 0.2% of release agent, 0.2-0.3% of platinum catalyst, 0.1-0.2% of inhibitor, and the balance being raw rubber; the raw rubber is composed of methyl vinyl silicone rubber and methylphenyl vinyl silicone rubber in a mass ratio of (7-8):(2-3); the silane coupling agent is γ-methacryloyloxypropyltrimethoxysilane; the release agent is zinc stearate; and the inhibitor is 3,5-dimethyl-1-hexyn-3-ol.

3. The flame-retardant and fire-resistant silicone rubber material according to claim 1, characterized in that: The composite flame retardant filler is made of the following raw materials in percentage by mass: 20-25% of ultrafine molybdenum disulfide with surface grafted carbon, 15-20% of hexagonal boron nitride nanosheets, 15-20% of ultrafine spherical alumina powder, 2-4% of ultrafine silicon nitride powder, 6-8% of nano calcium carbonate, 6-8% of nitrogen-phosphorus flame retardant FR-103, 6-8% of ultrafine aluminum hydroxide, 6-8% of ultrafine magnesium hydroxide, 0.8-1.5% of nano zinc oxide, and the balance is hollow glass microspheres.

4. The flame-retardant and fire-resistant silicone rubber material according to claim 1, characterized in that: The composite flame retardant filler is made of the following raw materials in percentage by mass: 24% of ultrafine molybdenum disulfide with carbon grafted on the surface, 16% of hexagonal boron nitride nanosheets, 18% of ultrafine spherical aluminum oxide powder, 3% of ultrafine silicon nitride powder, 8% of nano calcium carbonate, 6% of nitrogen-phosphorus flame retardant FR-103, 6% of ultrafine aluminum hydroxide, 6% of ultrafine magnesium hydroxide, 1% of nano zinc oxide, and 12% of hollow glass microspheres.

5. The flame retardant and fire resistant silicone rubber material according to claim 1, characterized in that: The viscosity of the hydrogen-containing silicone oil is 20-160 mPa·s, and the hydrogen content is 0.028-0.12 wt%; the viscosity of the vinyl silicone oil is 50-2000 mPa·s, and the vinyl content is 0.08-0.80 MMOL / G; the viscosity of the hydroxy silicone oil is 20-70 cst, and the hydroxyl content is 1.25-10%; the viscosity-average molecular weight of the methyl vinyl silicone rubber is 400,000-950,000, and the vinyl content is 0.07-0.7%; the viscosity-average molecular weight of the methyl phenyl vinyl silicone rubber is 400,000-800,000, the phenyl content is 2.5-20%, and the vinyl content is 0.15-0.5%.

6. A method for preparing the flame-retardant and fire-resistant silicone rubber material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: placing accurately measured composite flame retardant filler and silane coupling agent in a kneader and pre-kneading for 15-30 minutes to obtain a composite flame retardant filler with a surface modified by a silane coupling agent; Step 2: Heat-treat the accurately measured composite flame retardant filler modified with a surface silane coupling agent, carbon black, and raw rubber in a kneader at 180-200° C. for 150-180 minutes, mix them evenly, and cool them to room temperature for later use; Step three, the rubber material in step two is mixed evenly with accurately measured release agent, platinum catalyst, inhibitor, hydrogen silicone oil, vinyl silicone oil, and hydroxy silicone oil on a planetary mixer to obtain a mixed rubber, and the obtained mixed rubber is transferred to a flat plate vulcanizer and vulcanized at 120-160°C to obtain a finished flame retardant and fire-resistant silicone rubber material.

7. The method for preparing a flame-retardant and fire-resistant silicone rubber material according to claim 6, characterized in that: After the mixed rubber obtained in step 3 is transferred to a flat plate vulcanizer, a parallel plate capacitor is set on the flat plate vulcanizer so that the mixed rubber is located between the two plates of the parallel plate capacitor. The electric field direction of the parallel plate capacitor is perpendicular to the horizontal direction of the vulcanizing plate of the flat plate vulcanizer. The field strength E of the parallel plate capacitor is 2.0*10 3 -5.0*10 4 Newton / Coulomb, during the flat plate vulcanization process, the positive and negative poles of the power supply connected to the two plates in the parallel plate capacitor are cycled every 400-600 seconds, and the duration is 90-120 minutes.

Citation Information

Patent Citations

  • Waterborne heat-insulating fireproof coating for cables

    CN106280777A

  • Thermosetting resin composition and use thereof

    CN107163505A

  • High-strength and high-flame-retardant organic silicon foam material and preparation method thereof

    CN111378285A

  • Flame-retardant insulating silicone rubber and preparation method thereof

    CN113637328A

  • Flame-retardant reinforced cable

    CN115505195A